The Needs of Covid-19 Patients Admitted In Intensive Care Unit Based On Cultural Aspect - Ifa Hafifah; Tina Handayani Nasution (Universitas Faletehan, 2022)
A lot of needs of intensive care unit (ICU) patients were not met due to the limited time of interaction between patients and health workers. The unfulfilled needs of the patient further made their immune system weaken so that they took longer time to recover. The purpose of this study was to explore the needs of Covid-19 patients treated in ICU based on cultural aspects. This research used qualitative approach with descriptive phenomenological design. The data collection used google form. The samples were 5 nurses who treated Covid-19 patients in ICU, who were selected by using purposive sampling technique. Five major themes were generated by thematic content analysis, namely: (1) fulfillment of patients’ physical needs; (2) fulfillment of patient's psychological needs; (3) fulfillment of patient's cultural needs; (4) fulfillment of patient's spiritual needs; (5) fulfillment of patient's social needs. The researchers recommended further research on patients’ need questionnaire and expected health workers to meet the needs of patients physically, psychologically, spiritually, socially, and culturally.